Cuci Kampung as a Mechanism of Restorative Justice: Integrating Customary Law and Islamic Principles in the Rejang Lebong, Indonesia - Mabrur Syah; Habiburrahman Habiburrahman; Sri Wihidayati; Sidiq Aulia; Humaira Ahmad (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines the Cuci Kampung tradition among the Rejang community in Rejang Lebong as a form of religious and cultural law enforcement rooted in local wisdom. The primary focus is on how this tradition functions as a restorative, educational, and spiritual mechanism for resolving customary violations through the Jenang Kutei Customary Court. A normative-empirical method was employed, which combines document studies, field observations, and interviews with customary and religious leaders to analyse the interaction between Islamic and customary norms within a plural legal system. The findings reveal that Cuci Kampung and Jenang Kutei serve as a form of living law that integrates customary and Islamic values, such as justice, repentance, and social responsibility. The implementation of John Griffiths’ theory of legal pluralism clarifies how religious-cultural practices strengthen community-based justice systems. This research contributes to reinforcing models of restorative justice, which is grounded in local culture and provides a reference for integrating customary law into the formal legal system, as well as preserving local traditions as part of the development of national law.